A review of energy intake measures used in young children with cerebral palsy - Walker, J.; Bell, K.; Caristo, F.; Boyd, Roslyn; Davies, P. (2011)
The aim of this review was to evaluate the psychometric properties and clinical utility of energy intake measures used in young children with cerebral palsy (CP). Five databases were searched for relevant literature, and measures were included if they (1) directly measured energy intake in kilojoules/kilocalories per day; (2) had published data in kilojoules/kilocalories per day for children with CP from birth to 5 years; and (3) at least 40% of participants had a diagnosis of CP. Three measures met criteria: a 3-day weighed food record, a 3-day estimated food record, and a 7-day estimated food record. Included measures were evaluated on their characteristics, intended outcome, and validity. Reliability and responsiveness were not reported for any measure. Currently there is no dietary methodology that has proven reliability or repeated validity in young children with CP. Clinicians and researchers should not rely on current methodologies until further evaluation.